Analisis Kinerja Sistem Informasi Data Korporasi Jasa Raharja (DASI-JR) dengan menggunakan Metode PIECES - Ni Made Dewi Widiastuti; Satrio Hadi Wijoyo; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Jasa Raharja data (DASI-JR) is an information system used to help manage service and financial data at PT. Jasa Raharja (Persero). This system is a database-based application that integrates data. The implementation of the Kediri representative, provides ease of payment of traffic accidents so as to facilitate the community in the disbursement of accident compensation funds. Problem instant applied tie-JR is (1) if server down service will cease; (2) Because the service stops, the data input process will be repeated from scratch; (3) In some processes still manual such as Laka data or police accident data; (4) Because Laka data is manual, some service processes do not run (5) The process of service is not running causing decreased operational process performance; (6) The simultaneous use of usernames causes data input errors. Based on the description, this study of the performance analysis of the TIE-JR information System used the methods of analysis of PIECES (Performance, Information, Economic, Control, Eficiency and Sevice) of the corporate Data Information System Services Raharja (DASI-JR). Data collection techniques with questionnaires and population characteristics in this study as many as 22 respondents then conducted a descriptive statistical analysis. Based on PIECES analysis shows that the overall mean result is 3.92. On the performance mean of 4.01, above the overall mean value. In the information variable mean of 4.11, above the overall mean value. In the economic mean variable of 3.78, it is below the overall mean value. In the variable control mean of 3.88, it is below the overall mean value. At a variable efficiency mean of 3.94, above the overall mean value. In the service mean variable of 3.75, it is below the overall mean value. The economic, control and service variables can be concluded as a top priority for repairs, if viewed from the overall mean.